Topical application of 1% ZnSO4 on oral ulcers increases the number of macrophages in normal or diabetic conditions of wistar rats - Rochman Mujayanto; Kus Harijanti; Iwan Hernawan (Dental Journal (Majalah Kedokteran Gigi), 2016)
Background: Therapy for chronic ulcer in diabetic patient is by modifying local inflammation response using drugs that acts as immunomodulator, neuromodulator and growth factors stimulator. Topical zinc is one of drug that can modifiy local inflammation response, immunostimulation or immunosuppresion. Purpose: This study was to prove about the number of macrophage in oral ulcer between normal and diabetes microscopically and the difference if treated by 1% ZnSO4 gel topically. Method: Ulcer in lower labial mucosa was made in normal and diabetic Wistar rats (induced by STZ), then applied 1% ZnSO4 gel and CMC-Na gel as control. They were decapitated in third and fifth day and specimen was made by processing lower labial mucosa Result: Microscopically, the result showed the number of macrophages in oral ulcer in diabetic condition was significantly higher than normal and the application of 1% ZnSO4 increased the number of macrophages in fifth day. Conclusion: The number of macrophages was higher in diabetic than normal condition, and was proven that topical application of 1% ZnSO4 increased the number macrophages of oral ulcer diabetic and normal condition.